Pengaruh Kompensasi terhadap Kinerja Guru di Madrasah Ibtidaiyah Negeri 2 Bandung Barat - Muhammad Wildan Fauzi Nur; Aminuddin Irfani (Bandung Conference Series: Business and Management, 2022)
Abstract. This study aims to determine the effect of compensation on teacher performance at Madrasah Ibtidaiyah Negeri 2 West Bandung. This research is categorized as descriptive study and quantitative approach with questionnaire as the instrument. Populations in this study are 34 teachers. The sampling process is conducted using saturation sampling technique. The data collection process is conducted using questionnaires and observations. The instrument’s validity test is conducted using product moment pearson while the reliability test using Cronbach Alpha with the assistance of SPSS. The measuring instrument is proven to be valid and reliable to be used as the research instrument. This study’s hypothesis test is conducted using simple linear regression analysis The results show that compensation have no effect and is significant on teacher performance with a value of 1,362 and sig of 0,183 . Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Kompensasi Terhadap Kinerja Guru di Madrasah Ibtidaiyah Negeri 2 Bandung Barat. Penelitian ini dikategorikan sebagai penelitian deskriptif dan pendekatan kuantitatif dengan instrument berupa kuesioner. Populasi dalam penelitian ini adalah guru sebanyak 34 orang. Pengambilan sampel dengan menggunakan Teknik sampling jenuh. Pengumpulan data menggunakan kuesioner dan observasi. Uji validitas instrument dengan menggunakan product moment pearson sedangkan uji reabilitas dengan cronbanch Alpha dengan bantuan SPSS. Alat ukur terbukti valid dan reliable untuk instrument penelitian. Uji hipotesis penelitian ini menggunakan analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa kompensasi tidak memiliki pengaruh dan signifikan terhadap kinerja guru dengan nilai 1.362 dan sig 0,183.